2015
DOI: 10.1007/s00586-015-4349-4
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study comparing the serum levels of pro- or anti-inflammatory cytokines in patients with lumbar radicular pain and healthy subjects

Abstract: These findings support our hypothesis that sciatica pain is accompanied by the imbalance in inflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 32 publications
2
79
2
6
Order By: Relevance
“…Multiple studies have observed significant differences in proinflammatory cytokines (e.g., IL‐6, TNF‐α, IL‐8, and IL‐1β) in relation to pain intensity. By grouping patients on the basis of severity of patient‐reported outcomes (e.g., pain), it was found that serum protein levels and serum mRNA levels of IL‐6, IL‐8, and TNF‐α are all significantly higher in patients who experience categorically worse levels of LBP . Uçeyler et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple studies have observed significant differences in proinflammatory cytokines (e.g., IL‐6, TNF‐α, IL‐8, and IL‐1β) in relation to pain intensity. By grouping patients on the basis of severity of patient‐reported outcomes (e.g., pain), it was found that serum protein levels and serum mRNA levels of IL‐6, IL‐8, and TNF‐α are all significantly higher in patients who experience categorically worse levels of LBP . Uçeyler et al .…”
Section: Resultsmentioning
confidence: 99%
“…IL‐6 and IL‐8 were both found to be greater in severe sciatica patients compared not only with controls but also with mild sciatica patients, suggesting that proinflammatory cytokine levels may contribute to sciatica intensity. IL‐6 was also positively correlated with somatic dysfunction ( r = 0.394, P = 0.013) as measured by the Oswestry Disability Index (ODI) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations could explain our previous study, which showed that the TNF-α blood protein levels in the sciatica group were significantly higher than in healthy subjects 24. However, this sensitization could not be concluded to be a result of the direct phosphorylation or ubiquitylation of SLICK channels by p38 MAPK.…”
Section: Discussionmentioning
confidence: 63%